Microbiome-proteome analysis of gastrointestinal microbiota and longissimus thoracis muscle proteins in cattle with high and low grades of marbling - Mingyan Shi; Zhichao Li; Shuaishuai Hu; Pei Zhang; Shuaitao Meng; Luyao Huang; Zhiguo Miao; Jinzhou Zhang (BMC Veterinary Research)
Abstract Marbling is a key indicator of the meat quality of ruminants. Gastrointestinal microbiota may regulate the formation of marbling by influencing the nutritional metabolism of animals. This study analyzed the composition and functional differences of microbiota in the rumen and cecum, the differences in volatile fatty acids (VFAs) content in the longissimus thoracis muscle, and the differences in protein abundance in the longissimus thoracis muscle of ruminants with different marbling grades through microbiome-proteome analysis. The results showed that the diversity of gastrointestinal microbiota in high-marbling ruminants was significantly higher than that in low-marbling ruminants. The relative abundance of Firmicutes and Akkermansia in the gastrointestinal of high-marbling ruminants was higher than that in low-marbling ruminants, while the relative abundance of Bacteroidetes and Prevotella was lower. In addition, PICRUST2 functional prediction results of the microbiota revealed that the gastrointestinal microbiota of high-marbling ruminants was mainly involved in the biosynthesis pathways of fat and lipids. The metabolomics results showed that the content of VFAs (acetic acid, propionic acid, butyric acid, isovaleric acid, valeric acid, and hexanoic acid) in the rumen of high-marbling ruminants was significantly higher than that in low-marbling ruminants. The proteome analysis results indicated that the differential proteins in the longissimus thoracis muscle of high-marbling ruminants were mainly involved in lipid transport and metabolism compared to low-marbling ruminants. In summary, the differences in the composition and function of the gastrointestinal microbiota led to higher levels of VFAs in the gastrointestinal tract of high-marbling ruminants, which provides the basis for lipid/fat synthesis. The proteome results of the longissimus thoracis muscle support the view that high-marbling ruminants have richer lipid transport and metabolic functions in their muscle.